A124 THE DIAGNOSTIC ACCURACY OF BLOOD AND TISSUE-BASED TESTS FOR CYTOMEGALOVIRUS REACTIVATION IN INFLAMMATORY BOWEL DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (1st March 2018) - Tandon, P; Shukla, T; James, P D; Mallick, R; McCurdy, J
Abstract: Background: Several diagnostic techniques exist to detect cytomegalovirus (CMV) reactivation in inflammatory bowel disease (IBD). The accuracy of these tests compared to one another remains poorly defined. Aims: As such, the aim of this study was to compare the sensitivity and specificity of diagnostic tests for CMV reactivation in IBD. Methods: Multiple electronic databases were searched through July 2015 for cross-sectional and cohort studies comparing the accuracy (sensitivity and specificity) of at least two diagnostic tests for CMV reactivation in IBD. Initially, the accuracy of blood-based tests (whole blood PCR (bPCR) or pp65 antigenemia assay) was determined using tissue-based tests (tissue PCR (tPCR), immunohistochemistry (IHC) or hemotoxylin and eosin (H&E)) as the reference standard. Next the accuracy of individual tissue-based tests was assessed. Weighted summary estimates were determined by bivariate analysis, with random-effects or fixed-effects modelling when appropriate. Individual study quality was assessed by the QUADAS-2 tool. Results: Twelve studies compared blood-based tests (6 by bPCR, 5 by pp65, 1 by both) with tissue-based tests. The overall sensitivity and specificity of blood-based tests was 65% (95% CI, 31–99%) and 92% (95% CI, 89–96%) respectively. The sensitivity of bPCR was 63% (95% CI, 51–76%), and the sensitivity of pp65 antigenemia was 39% (95% CI, 27–52%). Eight studies compared histopathology (5 by H&E and 4 by IHC) with tPCR. The sensitivity of H&E was 6.2% (95% CI, 2.2–16.3%), and the sensitivity of IHC was 28.3% (95% CI, 12.2–52.8%) when compared to tPCR as the reference standard. Specificity was high for H&E (98.1%; 95% CI, 94.2–99.4%), and IHC (98.0%; 95% CI, 92.2–99.5%). Studies were limited by low study quality and in the ability to compare clinically relevant CMV reactivation. Conclusions: Our study demonstrates that blood-based tests and H&E are insensitive markers for CMV reactivation in IBD and should not be used as sole diagnostic tests. Funding Agencies: None